Impacts of thermos-physical properties on plate-fin multi-stream heat exchanger design in cryogenic process for CO2 capture. (25th February 2019) - Tan, Yuting; Nookuea, Worrada; Li, Hailong; Thorin, Eva; Yan, Jinyue
Abstract: Oxy-fuel combustion is one of the most promising technologies for CO2 capture for power plants. In oxy-fuel combustion plants, cryogenic process can be applied for CO2 purification because the main impurities in flue gas are non-condensable gases. The multi-stream plate-fin heat exchanger is one of the most important components in the CO2 cryogenic system. In-depth understanding of the impacts of property on the heat exchanger is of importance for appropriate design. In order to investigate the impacts of properties on sizing the heat exchanger and to further identify the key properties to be prioritized for the property model development, this paper presented the design procedure for the plate-fin multi-stream heat exchanger for the CO2 cryogenic process. Sensitivity study was conducted to analyze the impacts of thermos-physical properties including density, viscosity, heat capacity and thermal conductivity. The results show that thermal conductivity has the most significant impact and hence, developing a more accurate thermal conductivity model is more important for the heat exchanger design. In addition, even though viscosity has less significant impact compared to other properties, the larger deviation range of current viscosity models may lead to higher uncertainties in volume design and annual capital cost of heat exchanger.